Health and happiness: cross-sectional household surveys in Finland, Poland and Spain - Marta Miret; Francisco Félix Caballero; Somnath Chatterji; Beatriz Olaya; Beata Tobiasz-Adamczyk; Seppo Koskinen; Matilde Leonardi; Josep Maria Haro; José Luis Ayuso-Mateos (The World Health Organization, 2014)
Objective To explore the associations between health and how people evaluate and experience their lives. Methods We analysed data from nationally-representative household surveys originally conducted in 2011-2012 in Finland, Poland and Spain. These surveys provided information on 10 800 adults, for whom experienced well-being was measured using the Day Reconstruction Method and evaluative well-being was measured with the Cantril Self-Anchoring Striving Scale. Health status was assessed by questions in eight domains including mobility and self-care. We used multiple linear regression, structural equation models and multiple indicators/multiple causes models to explore factors associated with experienced and evaluative well-being. Findings The multiple indicator/multiple causes model conducted over the pooled sample showed that respondents with younger age (effect size, β = 0.19), with higher levels of education (β = −0.12), a history of depression (β = −0.17), poor health status (β = 0.29) or poor cognitive functioning (β = 0.09) reported worse experienced well-being. Additional factors associated with worse evaluative well-being were male sex (β = −0.03), not living with a partner (β = 0.07), and lower occupational (β = −0.07) or income levels (β = 0.08). Health status was the factor most strongly correlated with both experienced and evaluative well-being, even after controlling for a history of depression, age, income and other sociodemographic variables. Conclusion Health status is an important correlate of well-being. Therefore, strategies to improve population health would also improve people's well-being.